The Relations among Environmental Performance, Environmental and Firm Performance - Alia Ariesanti (The Indonesian Journal of Accounting Research, 2017)
Abstract: Companies tend to disclose good news. If the company has good environmental performance, it will be disclosed in the financial statements. This disclosure of environmental information will enhance the reputation of the company; thus it will increase company performance. The research aims to reexamine the results of the previous study by analyzing the environmental disclosure as mediating the relationship between environmental performance and corporate performance. The archival research method is applied in this study. This study is investigate manufacturing companies listed in Indonesia Stock Exchange and listed in the PROPER program in 2011. The finding implies that the performance of the environmental effect on the company's performance through environmental disclosure.Abstrak: Perusahaan cenderung mengungkapkan berita baik. Jika perusahaan memiliki kinerja lingkungan yang baik, maka akan diungkapkan dalam laporan keuangan. Pengungkapan informasi lingkungan ini akan meningkatkan reputasi perusahaan; sehingga akan meningkatkan kinerja perusahaan. Penelitian ini bertujuan untuk menguji kembali hasil penelitian sebelumnya dengan menganalisis pengungkapan lingkungan sebagai mediasi hubungan antara kinerja lingkungan dan kinerja perusahaan. Metode penelitian arsip diterapkan dalam penelitian ini. Penelitian ini adalah menyelidiki perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia dan terdaftar dalam program PROPER pada tahun 2011. Penemuan ini menyiratkan bahwa kinerja efek lingkungan pada kinerja perusahaan melalui pengungkapan lingkungan.